Identification of The Puerperium Infection Characteristics - Susilawati Susilawati; Kasron Kasron (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
The puerperium can caused puerperium infections. The puerperium infection can cause maternal death and increase the MMR rate. The research aims to determine the characteristics of puerperal infections in Cilacap Hospital at 2016-2018. The research was conducted in Cilacap Hospital, with a retrospective descriptive approach using medical records. Total sampling used when in the period of 2016-2018, were had 35 respondents Data analysis using univariate of the characteristic. The results showed that the age of patients who experienced puerperal infection averaged at age 29.8 years, average Hb levels of 10.8 mg / dl, mostly high school 62.9%, all respondents were housewives, the financing used was almost entirely BPJS 85.7%, where 60% BPJS-PBI, and 25.7% BPJS-non PBI, almost all SC 71.4%, most gave birth to the first child 51.4%, during pregnancy none of the respondents experienced a history of pregnancy complications 57.1%, and identification of puerperal infections in the most respondents was post SC operation infection 34.3%. Need further research on supporting interventions to overcome the signs of puerperal infection symptoms.